John Hejduk’s Pursuit of an Architectural Ethos - Martin Søberg (Footprint)
Reflected, artistic practices and design-based research are drastically expanding fields within architectural academia. However, the interest in uniting theory and practice is not entirely new. Just a few decades ago, before a ‘death of theory’ was proclaimed, questions of architectural epistemology, of the language(s) of architecture, were indeed of profound interest to the discipline.